2017
DOI: 10.1177/2325967117710759
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Injuries in Stand-Up Paddle Boarding

Abstract: Background:Stand-up paddle boarding (SUP) is a recreational activity and sport that has grown exponentially, with participation increasing from 1.1 million in 2010 to 2.8 million in 2014 in the United States alone. Despite this growth in participation, SUP remains underresearched with regard to injury epidemiology.Purpose:To investigate injury epidemiology (severity, location, type, mechanism) in SUP.Study Design:Descriptive epidemiology study.Methods:An open-source online survey was administered to active SUP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 22 publications
7
46
1
6
Order By: Relevance
“…The reduced hip motion, combined with greater shoulder movement, illustrates a tendency for the inexperienced group to rely heavily on the shoulder and possibly the biceps and forearm musculature to generate force during the entry and drive phases of the stroke. It is unclear at this stage whether this may predispose the shoulder and elbow to injury, both of which were shown to be a common site of injury in SUP paddlers (Furness et al, 2017). In contrast, the experienced participants had less overall shoulder ROM and greater hip ROM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced hip motion, combined with greater shoulder movement, illustrates a tendency for the inexperienced group to rely heavily on the shoulder and possibly the biceps and forearm musculature to generate force during the entry and drive phases of the stroke. It is unclear at this stage whether this may predispose the shoulder and elbow to injury, both of which were shown to be a common site of injury in SUP paddlers (Furness et al, 2017). In contrast, the experienced participants had less overall shoulder ROM and greater hip ROM.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical analysis in sport allows for modifications to technique in order to maximize power output and minimize injury (Ho, Smith & O’Meara, 2009; Bini & Carpes, 2014). Epidemiological studies of injuries in SUP have revealed that the shoulder/upper arm (32.9%) lower back (14.3%) and elbow/forearm (11.8%) were the most common locations of injuries reported in a study of both competitive and recreational SUP riders (Furness et al, 2017). The importance of technique is highlighted by the fact that less than optimal stroke biomechanics has been associated with both shoulder, elbow and back injuries in the similar sports of kayaking, and outrigger paddling (Hagemann, Rijke & Mars, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Without this level of instruction, a paddler may be more prone to injury. Injuries associated with SUP participation are thought to include the elbow, shoulder and back, and could be due to improper technique and inadequate training [ 4 , 24 ]. Given that the primary reason people use a SUP is for fun and fitness, SUP may be an ideal activity to promote to address the problem with inactivity amongst Australians.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that dynamic balance ability can be significantly improved after 30 minutes of SUP training on water [10]. Furness et al [7] also demonstrated that elite stand-up paddlers had more favorable static balance than recreational paddlers did, indicating that an SUP workout can achieve core strengthening after long-or short-term training to improve balance ability. In the kneeling position, because trunk and lower limb movements are limited, the main source of paddling power is the upper arm force.…”
Section: Application In Sup Course Teachingmentioning
confidence: 99%
“…Although SUP is also generally regarded as an effective full-body workout, few studies are in progress, and little scientific evidence can confirm these benefits. Studies related to SUP have included only research on topics such as sports injury epidemiology [6][7][8], body composition analysis, and respiratory metabolism [9][10][11][12]. Other studies have analyzed the effectiveness of exercise training intervention [13,14].…”
Section: Introductionmentioning
confidence: 99%